국내 홈네트워크 산업의 참여사업자의 비즈니스 모델 분석 - 노미진(Mi-Jin Noh); 김주성(Ju-Seong Kim) (한국콘텐츠학회 논문지, 8(9), 2008)
The purpose of this study analyzes services and the markets creating the profit of the national home network industry and the promotion strategy will be proposed. First, the technologies and products of the home network industry are analyzed, and the value chain of this industry is grasped. Second, the home network industry is classified into the communication common carrier, the construction carrier, the content/solution carrier, and the electronic business carrier. Third, The business model of the home network industry reconstructed based on the researches of Morris et al.(2005) and Chesbrough and Rosenbloom(2002), and the strategies are analyzed. We performed the industrial analysis as the company environment analysis, factor analysis of the value creation, business strategy analysis and so on. 본 연구는 국내 홈네트워크 산업의 수익을 창출할 수 있는 서비스와 시장을 분석하여 활성화 전략을 제안하는 것이다. 우선 국내 홈네트워크 기술 및 제품을 분석하여 홈네트워크 산업의 가치사슬을 파악한 후, 국내 시장의 성장가능성을 측정한다. 둘째, 홈네트워크 산업을 통신사업자, 건설사업자, 컨텐츠/솔루션사업자, 전자업체로 분류한다. 셋째, 비즈니스 모델의 구성요소를 기반으로 산업별 홈네트워크 산업의 비즈니스 모델을 분석하여 홈네트워크 산업의 활성화 전략을 분석하는 것이다. 홈네트워크 비즈니스 모델은 Morris 등(2005)과 Chesbrough & Rosenbloom(2002)의 연구를 기반으로 재구성하였으며, 기업 환경 분석, 가치창출 요인 파악, 사업전략 분석, 수익과 비용 구조 파악, 포지션 분석, 경쟁 우위 요인 분석, 실행 순으로 업종별 분석을 수행하였다. 홈네트워크 산업의 활성화 전략을 파악하기 위해서 원가우위 전략, 차별화 전략, 제휴 전략을 분석하였다.